1999
DOI: 10.1161/01.cir.99.2.211
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Mapping of Activation Through an Incomplete Isthmus Ablation Line

Abstract: Background-Activation mechanisms through gaps in ablation lines and resulting electrograms are poorly understood. Methods and Results-Eight patients (all men; age, 59Ϯ9 years) were studied during a recurrence of typical atrial flutter (cycle length, 233Ϯ19 ms) after a previous catheter ablation in the cavotricuspid isthmus. High-density 3-dimensional mapping of the isthmus was performed with the Cordis-Biosense EP Navigation system, and local conduction velocity (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 26 publications
0
43
1
Order By: Relevance
“…Shah et al described slow conduction through the isthmus created by incomplete ablation causing sustained stable AFL. 22 Avoidance of incomplete ablation could prevent incisional macroreentry after the Maze procedure. Nonpulmonary vein focal tachycardia may also occur after the Maze procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al described slow conduction through the isthmus created by incomplete ablation causing sustained stable AFL. 22 Avoidance of incomplete ablation could prevent incisional macroreentry after the Maze procedure. Nonpulmonary vein focal tachycardia may also occur after the Maze procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Double potentials separated by an isoelectric interval have been shown to indicate local block under the recording dipole, each component of the double potential reflecting the asynchronous activation on either side of the block [11][12][13][14][15] . As shown by Shah et al [10] double potentials may be observed in incomplete block, therefore, their recording in itself is insufficient to conclude that double potentials are related to complete block. During recurrent flutter, double potentials with an isoelectric interval localized a zone of local conduction block produced by a partial line of RF lesions, whereas merging double potentials leading to single or fractionated electrograms localized a RF: radio frequency ablation procedure, S-QRS interval: stimulus to QRS interval was the duration of the interval between the pacing artefact during low atrial pacing and the summit of the R wave in surface lead II.…”
Section: Discussionmentioning
confidence: 90%
“…The stimulus to QRS interval (S-QRS) was the duration of the interval between the pacing artefact during low atrial pacing and the peak of the R wave in surface lead II. Double potentials were defined by two major deflections separated by an isoelectric interval d30 ms [10] and were recorded at high amplification (0·2 or 0·1 mV/cm). The measurement of the double potential duration has been taken from the earliest deflection of the first component of the double potential to the earliest deflection of the second component.…”
Section: Electrophysiological Studymentioning
confidence: 99%
See 2 more Smart Citations